Pamięć jako narzędzie walki w konfliktach etnicznych: Casus Irlandii Północnej (Politeja, 2014)
Is Social Memory used as a Weapon in Ethnic Conflicts? Northern Ireland CasusIn case of ethnic conflicts, groups may use memories or symbols of casualties or events which happened during conflict, as a specific symbolic weapon. Weapon addressed to the opponent, usually “the other” group defined as “enemy”, but inthe same time as a message addressed to “my” group. Visual displays of Ulster conflict – murals, flags and emblems, painted kerbstones – have been used not only to create patterns of social memory and remembering but also social‑ethnic group identity. These visual displays play significant role in constructing Belfast landscape and Belfast “ethnic identity”.